DMAP-stabilized bis(silyl)silylenes as versatile synthons for organosilicon compounds. Issue 6 (21st January 2020) - Holzner, Richard; Reiter, Dominik; Frisch, Philipp; Inoue, Shigeyoshi
Abstract : DMAP-stabilized silylenes 1a–c, which are convenient, room temperature stable synthetic equivalents for the corresponding highly reactive free bis(silyl)silylenes are reported. Abstract : DMAP-stabilized silylenes 1a–c are obtained from the reductive debromination of the corresponding dibromosilanes in the presence of DMAP. Their distinctly different thermal isomerization reactions via C–H bond activation, dearomative ring expansion and silyl migration are discussed. Furthermore, complexes 1 dissociate at elevated temperatures, providing the corresponding free silylenes in situ, which are even capable of single-site activation of H2 . Additionally, a potassium-substituted silicon-centered radical 2 is isolated from overreduction of ( t Bu3 Si)2 SiBr2 .